INCREASING CONSUMER PURCHASE INTEREST: THE ROLE OF SOCIAL MEDIA MARKETING AND TRUST IN MSMES IN BENGKULU CITY - Dapa Nugraha; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to analyze the effect of social media marketing and consumer confidence on buying interest in MSME products in Bengkulu City. A quantitative approach was used in this study with a survey method to collect data from respondents selected by purposive sampling. The research instrument is a questionnaire which is compiled based on the indicators of the research variables and measured using a Likert scale. The collected data were analyzed using statistical tests, including descriptive analysis and linear regression, to test the relationship between variables. The results showed that social media marketing has a positive and significant influence on consumer buying interest. In addition, consumer trust also plays an important role in increasing buying interest in MSME products. This research provides practical implications for MSME players to optimize marketing strategies through social media and build trust to increase product attractiveness in the local market.